A STUDY ON CARVEDILOL VERSUS METOPROLOL IN THE MANAGEMENT OF ATRIAL FIBRILLATION IN POST OPERATIVE CORONARY ARTERY BYPASS GRAFT SURGERY PATIENTS (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The objective of the present study is to analyse the effectiveness of carvedilol and metoprolol in the management of atrial fibrillation in post operative coronary artery bypass graft surgery patients. Atrial fibrillation occurs frequently soon after coronary artery bypass grafting and often results in increased mortality and morbidity. The incidence of post operative atrial fibrillation actually varies from 11% to 40% despite of the surgical technique and current guidelines recommend beta blockers as a medication for the prevention of atrial fibrillation after coronary artery bypass graft surgery. A prospective observational study was conducted on 100 subjects considering the inclusion and exclusion criteria and they were classified into carvedilol and metoprolol group. Heart rate was chosen as the primary parameter and statistical analysis was performed using student‘t’ test (p<0.05). There was a statistically significant decrease in the heart rate after therapy for both metoprolol and carvedilol but the difference in the effectiveness between carvedilol and metoprolol could not be significantly identified.